The Teaching Mode of Artificial Intelligence Enabling the Construction of Teachers in Private Colleges and Universities under the Network Environment - Han, Yunna (Transactions on Social Science, Education and Humanities Research, 2023)
This paper discusses the application of artificial intelligence in the field of education, including personalized learning and adaptive evaluation in the learning process, as well as the development and management of teaching resources, virtual experiment and distance teaching. At the same time, the paper points out the challenges facing the construction of teachers in private universities, and emphasizes the potential and significance of artificial intelligence to enable the construction of teachers in private universities. In the network environment, the teaching mode based on artificial intelligence includes teaching resource development and management, personalized learning and adaptive evaluation, virtual experiment and distance teaching, learning data analysis and personalized tutoring, etc. Finally, the paper proposes the importance of teacher training and support mechanism, in order to improve the AI education level and teaching effect of teachers.